Enhancing Student Administrative Services Through Integrated POAC Management Functions in Islamic Secondary Schools - Auliatul Maulida; Poppy Rachman; Nur Hayati (Journal of Educational Management Research, 2026)
This study aims to analyze the implementation of administrative management in improving student administrative services based on the four managerial functions of Planning, Organizing, Implementation, and Monitoring (POAC). A descriptive qualitative approach was employed to obtain an in-depth understanding of administrative management practices in an Islamic secondary school. Data were collected through semi-structured interviews, direct observations, and document analysis involving school leaders, administrative personnel, and students. The data were analyzed using the interactive model of data condensation, data display, and conclusion drawing and verification. The findings reveal that the four managerial functions have been implemented systematically. Planning is reflected in structured work programs and service schedules, organizing is supported by a clear distribution of responsibilities and collaborative coordination, implementation is characterized by responsive, orderly, and standardized administrative services, while monitoring is conducted through continuous supervision and periodic evaluation. Nevertheless, several challenges remain, including limited facilities, insufficient administrative personnel, increasing workloads, and delays in administrative data submission. These findings imply that strengthening integrated administrative management, supported by digital technology adoption, continuous staff development, and sustainable quality assurance, is essential for improving the effectiveness, efficiency, and sustainability of student administrative services in Islamic educational institutions.